Validation of career decision-making questionnaire for vocational accounting students using exploratory and confirmatory factor analysis - Eka Ary Wibawa; Ani Widayati; Arif Rahman Hakim; Arief Nurrahman (Universitas PGRI Madiun, 2025)
This study aims to validate a career decision-making instrument for vocational accounting students using a quantitative positivist approach. Data were collected from 134 respondents using a Likert scale questionnaire and analyzed through Exploratory Factor Analysis and Confirmatory Factor Analysis. The results reveal that career decision-making consists of four primary factors: career goals, career planning, career readiness, and self-assessment. Career planning was identified as the most dominant factor. The instrument was proven valid and reliable for measuring career decision-making skills in vocational accounting education.